2017
DOI: 10.1061/(asce)ei.1943-5541.0000331
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the Professional Development of Qualified Women in the Peruvian Construction Industry

Abstract: The construction industry frequently offers an unwelcoming environment for women, and those who do manage to enter have high rates of turnover and abandonment. Within this scenario, this research aims to identify the barriers faced by qualified women, to analyze the different views that qualified men and women have regarding these barriers, and to find the underlying factors that group these barriers and their degrees of importance. In the context of this research, "qualified" men and women are those who hold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…In recent research by Barreto et al (2017), 20 barriers were identified. These barriers composed the statements of the questionnaire survey and the data was obtained from 429 professionals in the Peruvian construction industry.…”
Section: Gender Roles and Barriers To Women In Constructionmentioning
confidence: 99%
“…In recent research by Barreto et al (2017), 20 barriers were identified. These barriers composed the statements of the questionnaire survey and the data was obtained from 429 professionals in the Peruvian construction industry.…”
Section: Gender Roles and Barriers To Women In Constructionmentioning
confidence: 99%
“…This was also important to kill the issues of possible bias that may arise when only female respondents are surveyed. Other female career progression-related studies in the construction industry have considered both men and women in their surveys (see Duong and Skitmore, 2003; Barreto et al , 2017; Bryce et al , 2019). Since the required number of such contractors was not readily available, the purposive and snowball sampling approaches (non-probability sampling approaches) were used to locate 80 Construction Project Managers working with 80 class D1 firms (50 in Accra and 30 in Kumasi).…”
Section: Methodsmentioning
confidence: 99%
“…It is noted that the literature on barriers faced by women in construction is growing in recent years (e.g., Barreto et al 2017;Ibáñez 2017;Oo, Feng and Lim 2019;Regis et al 2019;Oo, Liu and Lim 2020), this can partly be explained because women are seen as an untapped resource to meet the workforce demand for both professional roles and skilled tradesmen in the industry (Fielden et al 2000;Berik and Bilginsoy 2006;Menches and Abraham 2007). Needless to say, women in construction would have to face various challenges and difficulties in addressing career barriers, which are generally presented in a long list in the literature.…”
Section: Literature Review Women's Career In Construction In Pre-covid-19 Eramentioning
confidence: 99%